Reducing the dose of neuromuscular blocking agents with adjuncts: a systematic review and meta-analysis. (March 2021) - Weber, Valentin; Abbott, Tom E.F.; Ackland, Gareth L.
Abstract: Background: Acute global shortages of neuromuscular blocking agents (NMBA) threaten to impact adversely on perioperative and critical care. The use of pharmacological adjuncts may reduce NMBA dose. However, the magnitude of any putative effects remains unclear. Methods: We conducted a systematic review and meta-analysis of RCTs. We searched Medline, Embase, Web of Science, and Cochrane Database (1970–2020) for RCTs comparing use of pharmacological adjuncts for NMBAs. We excluded RCTs not reporting perioperative NMBA dose. The primary outcome was total NMBA dose used to achieve a clinically acceptable depth of neuromuscular block. We assessed the quality of evidence using the GRADE (Grades of Recommendation, Assessment, Development, and Evaluation) criteria. Data are presented as the standardised mean difference (SMD); I 2 indicates percentage of variance attributable to heterogeneity. Results: From 3082 records, the full texts of 159 trials were retrieved. Thirty-one perioperative RCTs met the inclusion criteria for meta-analysis ( n =1962). No studies were conducted in critically ill patients. Reduction in NMBA dose was associated with use of magnesium (SMD: –1.10 [–1.44 to –0.76], P <0.001; I 2 =85%; GRADE=moderate), dexmedetomidine (SMD: –0.89 [–1.55 to –0.22]; P =0.009; I 2 =87%; GRADE=low), and clonidine (SMD: –0.67 [–1.13 to –0.22]; P =0.004; I 2 =0%; GRADE=low) but not lidocaine (SMD: –0.46 [–1.01 to –0.09]; P =0.10; I 2 =68%; GRADE=moderate). Meta-analyses for nicardipine, diltiazem, and dexamethasone were not possible owing to the low numbers of studies. We estimated that 30–50 mg kg −1 magnesium preoperatively (8–15 mg kg h −1 intraoperatively) reduces rocuronium dose by 25.5% (inter-quartile range, 14.7–31). Conclusions: Magnesium, dexmedetomidine, and clonidine may confer a clinically relevant sparing effect on the required dose of neuromuscular block ing drugs in the perioperative setting. Systematic review registration: PROSPERO: CRD42020183969.